2023
DOI: 10.1039/d2ra07472a
|View full text |Cite
|
Sign up to set email alerts
|

How a single mutation alters the protein structure: a simulation investigation on protein tyrosine phosphatase SHP2

Abstract: Dissecting how and why a single E76K mutation alters the probability densities of the conformational ensemble of SHP2 with enhanced sampling metadynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…It was observed that SHP2 was more dynamic in the open state, and the E76K mutation significantly reduced the interaction between the N‐SH2 and PTP domains, leading to increased conformational flexibility. Therefore, the conformational shift induced by the E76K mutation could provide valuable insights for future drug design efforts targeting SHP2 (Hou et al, 2023). Another kinetic study suggests that Tyr66 mutations in the N‐SH2 domain of SHP2 and its surrounding residues: Asp40, Lys55 and/or Gln57 may disrupt SHP2 switching mechanisms and negatively affect Py‐peptide binding, providing new possibilities for the development of SHP2 inhibitors (Guvench et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that SHP2 was more dynamic in the open state, and the E76K mutation significantly reduced the interaction between the N‐SH2 and PTP domains, leading to increased conformational flexibility. Therefore, the conformational shift induced by the E76K mutation could provide valuable insights for future drug design efforts targeting SHP2 (Hou et al, 2023). Another kinetic study suggests that Tyr66 mutations in the N‐SH2 domain of SHP2 and its surrounding residues: Asp40, Lys55 and/or Gln57 may disrupt SHP2 switching mechanisms and negatively affect Py‐peptide binding, providing new possibilities for the development of SHP2 inhibitors (Guvench et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Giving weight to the latter possibility, the amount of N-SH2 buried surface area in SHP2open is quite small (357 Å 2 , compared to 1025 Å 2 in SHP2’s closed state), and the positioning of N-SH2 in SHP2open is partially fixed by crystal contacts between E76K SHP2 molecules, suggesting that the structure may be stabilized by the crystallization process. , Also, several studies have attempted to use molecular dynamics (MD) simulations to characterize SHP2’s open state, and the preponderance of the MD data suggests that SHP2 populates a range of open states when activated. For example, the results of Calligari et al suggest that the “active state of SHP2 is highly dynamic” and that “the position of the N-SH2 domain in the active state is not stabilized by strong interactions” . Along the same lines, modeling studies by Hou et al predict a range of open states that vary substantially both with respect to each other and to SHP2open (ranging from 6.9 to 19.7 Å in root-mean square deviation from SHP2open) . Finally, an open-state structure of SHP1, an enzyme highly homologous to SHP2, has revealed an alternative structure that is similar, but not identical, to SHP2open (e.g., SHP1’s SH2 rotation is 110°, as opposed to 120°). , In summary, it is unclear from the current literature whether SHP2open represents an atomic-level functional model for understanding SHP2 activation in solution.…”
Section: Introductionmentioning
confidence: 99%
“…25 Along the same lines, modeling studies by Hou et al predict a range of open states that vary substantially both with respect to each other and to SHP2open (ranging from 6.9 to 19.7 Å in root-mean square deviation from SHP2open). 26 Finally, an open-state structure of SHP1, an enzyme highly homologous to SHP2, has revealed an alternative structure that is similar, but not identical, to SHP2open (e.g., SHP1's SH2 rotation is 110°, as opposed to 120°). 18,28 In summary, it is unclear from the current literature whether SHP2open represents an atomiclevel functional model for understanding SHP2 activation in solution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme dynamically transitions between a closed (basal) state, where the N-SH2 domain occludes the PTP catalytic cleft, and an open (active) state, triggered by activating mutations or ligand binding C-SH2 domain, represents a conformational change of unusual magnitude that has garnered significant research attention [11][12][13][14]. Nuclear magnetic resonance (NMR) spectroscopy and molecular dynamics simulations have been instrumental in elucidating the key transition states and pathways underlying SHP2's allosteric regulation [12,[15][16][17]. Recent investigations, employing molecular dynamics simulations and small-angle X-ray scattering (SAXS), have revealed unexpected flexibility within the open state of the E76K mutant, a model system for studying SHP2 activation [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%